2021
DOI: 10.1016/j.jbc.2021.101314
|View full text |Cite
|
Sign up to set email alerts
|

The copper chaperone CCS facilitates copper binding to MEK1/2 to promote kinase activation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Such parameters include verification of the stoichiometry of PERK-copper binding, the affinity of this interaction, and the redox state of copper when bound. The cellular environment of the cytosol, and the conditions required for PERK-copper interaction in our in vitro studies suggest that PERK binds copper it its cuprous (I) state, and that, unlike other recently characterized copper binding enzymes, it is unable to bind or reduce cupric (II) copper (Attar et al, 2020;Grasso et al, 2020;Grasso et al, 2021). However, further biophysical studies utilizing electron paramagnetic resonance (EPR), Xray absorption spectroscopy (XAS), and extra X-ray absorption fine structure (EXFAS) would be required to confirm these hypotheses by absence of a detectable copper II bound state.…”
Section: Figure 4-copper Manipulation Can Modulate Er Stress Tolerancementioning
confidence: 75%
See 1 more Smart Citation
“…Such parameters include verification of the stoichiometry of PERK-copper binding, the affinity of this interaction, and the redox state of copper when bound. The cellular environment of the cytosol, and the conditions required for PERK-copper interaction in our in vitro studies suggest that PERK binds copper it its cuprous (I) state, and that, unlike other recently characterized copper binding enzymes, it is unable to bind or reduce cupric (II) copper (Attar et al, 2020;Grasso et al, 2020;Grasso et al, 2021). However, further biophysical studies utilizing electron paramagnetic resonance (EPR), Xray absorption spectroscopy (XAS), and extra X-ray absorption fine structure (EXFAS) would be required to confirm these hypotheses by absence of a detectable copper II bound state.…”
Section: Figure 4-copper Manipulation Can Modulate Er Stress Tolerancementioning
confidence: 75%
“…In a series of studies they specifically delineated the residues involved in copper binding as well as the copper binding affinity and stoichiometry of MEK. In follow-up they demonstrated that copper binding is required for MEK activity, such that copper manipulations, including chelation, could be used to modulate MEK1/2 activity, including to therapeutic benefit in cancer models (Brady et al, 2014; Grasso et al, 2020; Grasso et al, 2021; Turski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the physiological role of copper on kinase activity has the added intricacy of determining the cellular mechanism of copper delivery. A recent study established that CCS delivers copper to MEK1, thereby modulating the signaling activity of MEK1 ( Grasso et al, 2021 ). However, the copper delivery mechanism for CK2 is unknown, and whether CCS serves in this capacity or whether another chaperone is involved has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the focus moved to the research of the copper chaperone in charge of delivering the metal to MEK1. Grasso and colleagues recently demonstrated, by using surface plasmon resonance and proximity-dependent biotin ligase analyses, which CCS is the copper donor appointee of the copper transfer to MEK1 [ 69 ]. They further corroborated their findings by using a CCS small-molecule inhibitor or by introducing mutations in the CuI binding site of CCS.…”
Section: Copper-dependent Kinases and Their Pathological Roles In Cancermentioning
confidence: 99%